THEORETICAL FOUNDATION OF EUPHEMISM - Raxmanova Sarvinoz Alisherovna; Qulsoatova Zilola Rashidovna; Samadova Nigina Sherzod qizi (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Anotation:This article analyzes the theoretical foundations of euphemisms, their role and importance in language. Euphemisms are mild expressions used to soften negative, uncomfortable, or taboo topics. In the article, the main types of euphemism, its social, cultural and psychological aspects, as well as its importance in the process of communication are widely studied. It is intended to carefully analyze the place of euphemism in linguistics, its influence on language and its role in communication. Also, the article provides important information about the connection of euphemisms with social taboos and cultural norms and how they are used in language.